High Levels of Circulating Cell-free DNA Are Associated With a Poor Prognosis in Patients With Severe Fever With Thrombocytopenia Syndrome. (24th July 2019) - Zhang, Yue; Song, Rui; Shen, Yi; Zhao, Yongxiang; Zhao, Zhenghua; Fan, Tianli; Yang, Xiaoyu; Wang, Lin; Zhang, Wei; Chen, Chong; Tian, Di; Wang, Ying; et al.
Abstract: Background: The extensive geographical distribution and high mortality rate of severe fever with thrombocytopenia syndrome (SFTS) have made it an important threat to public health. Neutrophil extracellular traps (NETs) can be activated by a variety of pathogens and are associated with thrombocytopenia in viral infections. We aimed to identify NET production and its predictive value for disease progression and prognosis in patients with SFTS. Methods: A prospective study was performed with a multicenter cohort of patients with SFTS (n = 112) to quantify serum NET levels. Three markers of NETs—namely, cell-free DNA (cfDNA), myeloperoxidase-DNA complexes, and lactoferrin-DNA complexes—were measured with PicoGreen double-stranded DNA assays and enzyme-linked immunosorbent assays. Receiver operating characteristic curves and multivariate regression analyses were performed to calculate the predictive value of cfDNA levels. Results: SFTS was characterized by pronounced NET formation. The serum levels of NETs changed dynamically during disease progression, with an inverse pattern of the trends of platelet and neutrophil levels. High cfDNA levels were strongly associated with multiple pathological processes, including coagulopathy, myocardial damage, liver dysfunction, and the development of encephalopathy. A high level of cfDNA (>711.7 ng/mL) at the time of the initial diagnosis predicted severe illness in patients with SFTS (odds ratio, 8.285 [95% confidence interval, 2.049–33.503]; P = .003). Conclusions: This study has a high degree of clinical impact for identification of cfDNA as a useful predictive biomarker of clinical outcomes of SFTS. Abstract : We identified cell-free DNA (cfDNA) as a useful predictive biomarker of clinical outcomes of severe fever with thrombocytopenia syndrome. Serum levels of cfDNA significantly correlated with multiple pathological lesions and changed dynamically in the serum levels during disease progression.